To the knowledge of Vespidae (Hymenoptera) of Pakistan - Mahmood, Khalid; Ullah, Mishkat; Aziz, Abdul; Hasan, Syed Azhar; Inayatullah, Mian (Zootaxa, 2012)
Twenty-three species in eight genera are recorderd from Pakistan and two species in two genera are recorded from Bangladesh (former East Pakistan). Seven species Vespula nursei Archer, Polistes (Polistella) stigma tamulus (Fabricius), P. (Gyrostoma) olivaceus (De Geer), Ropalidia brevita Das & Gupta, R. cyathiformis (Fabricius), Ancistrocerus gazella (Panzer), and Anterhynchium flavomarginatum flavomarginatum (Smith) are newly recorded from Pakistan. Body length variability is given for all studied species. Four figures (habitus, head, mesosoma and metasoma ) are given for 22 species from Pakistan.